The attack on November 13, 2015: organisation of the medico-judicial unit of the Hôtel-Dieu Hospital in Paris - Nicolas Soussy; Laurène Dufayet; Caroline Rey-Salmon; Charlotte Gorgiard (Oxford University Press, 2020)
The main aims of a medico-judicial unit are to ensure the examination of assault victims or persons in custody and to perform sampling necessary for investigations. Forensic examination is essential to describe the wounds and to evaluate the consequences of an assault by determining days of total incapacity for work (ITT). After the Paris attack on November 13, 2015, 121 victims were examined at the medico-judicial units of Paris. An initial forensic certificate was issued by forensic physicians with an assessment of physical ITT. A consultation with a forensic psychiatrist was systematically scheduled on the same day to obtain a forensic certificate for the psychological ITT. The average age of the victims was (33 ± 7) years and the sex ratio was 1.26. Most victims were in the Bataclan concert hall (78/121 or 64.5%). Of the 121 victims, 73 (60.3%) had projectile lesions (bullets, bolts and nuts, metal fragments, etc.) and 48 (39.7%) had non-projectile lesions (bruises, hematomas, etc.). The average physical ITT was 27 days (0; 190). The evaluation of the number of days of physical ITT was often complicated as some patients were still in medical care at the time of the initial examination. This experience enabled the Paris medico-judicial unit to anticipate the management required should any future event of this magnitude occur. It also reinforced cooperation between the medico-judicial unit and other departments, mostly emergency services and the forensic psychiatric unit. The Paris medico-judicial unit was thus able to offer a unique place of care by providing both physical and psychological examinations.